GENERATION PEDAGOGICAL FUNDAMENTALS THE FORMATION OF AN INCLUSIVE EDUCATIONAL ENVIRONMENT IN HIGHER EDUCATION BY MEANS OF PHYSICAL EDUCATION - Blavt, Oksana; Kozibroda, Larysa; Rozhko, Elena (Mountain School of Ukrainian Carpaty, 2021)
The article considers the issue of inclusive educational environment in higher education in terms of current trends in Ukrainian society. It is established that an important step towards overcoming the problem of social adaptation and integration of people with special needs, as one of the key priorities of modern Ukrainian social and educational policy, is to provide such people with the opportunity to provide quality educational services. In the conditions of active search for effective solutions to such a situation, it seems expedient to study the possibilities of using physical education for the integration of persons with special educational needs into the educational environment of the higher education system. The purpose of the study is to identify and substantiate the pedagogical foundations of the formation of an inclusive educational environment in higher education by means of physical education. Research methods: theoretical analysis, systematization, comparison of different views on the researched problem, generalization of data of scientific-methodical and special literature. Results: It was found that the formation of an inclusive educational environment involves a radical revision of the theoretical and methodological foundations of physical education, elimination of organizational and methodological barriers, development and implementation of new modern approaches and technologies, implementation of inclusive physical education practices for students with special educational needs. The pedagogical conditions for ensuring the formation of an inclusive educational environment in higher education in the process of physical education: methodological support; the focus of the content on the implementation of inclusive approaches based on individual approach and differentiated approaches. Conclusions. The results of scientific research give grounds to state the inseparable relationship in the organization of an inclusive educational environment of learning and physical education. Prospects for improving this process in terms of using all the potentials of physical education are identified. The priorities of the pedagogical process of physical education, aimed at eliminating the existing negative trends in physical development and health of students with special educational needs are aimed at implementing inclusive approaches in the formation of pedagogical technologies of physical education.